2020
DOI: 10.3892/ijmm.2020.4580
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA PART1 promotes intervertebral disc degeneration through regulating the�miR‑93/MMP2 pathway in nucleus pulposus cells

Abstract: The aim of the present study was to investigate the role of the long non-coding (lnc)RNA PART1 in nucleus pulposus (NP) cells derived from patients with intervertebral disc degeneration (Idd). The level of PART1 in degenerative NP tissues from patients with Idd, bulging and herniated discs was measured by reverse transcription-quantitative PcR (RT-qPcR) analysis. NP cells were isolated from patients with Idd and transfected with siPART1, after which time the growth ability of the NP cells was evaluated by cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 40 publications
(38 reference statements)
1
20
0
Order By: Relevance
“…In the present study, the level of lncRNA PART1 expression was detected in 10 ng/ml LPS-stimulated NP cells. Previous reports have demonstrated that PART1 expression was upregulated in patients with IDD (17,18). In line with previous studies, the results of the present study indicated that the level of lncRNA PART1 was higher in LPS-stimulated NP cells compared with that in normal untreated cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, the level of lncRNA PART1 expression was detected in 10 ng/ml LPS-stimulated NP cells. Previous reports have demonstrated that PART1 expression was upregulated in patients with IDD (17,18). In line with previous studies, the results of the present study indicated that the level of lncRNA PART1 was higher in LPS-stimulated NP cells compared with that in normal untreated cells.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, lncRNA PART1 is a newly discovered lncRNA that has been previously reported to serve as either an oncogene or suppressor gene in tumors ( 14 , 26 , 37 ). Accumulating studies have suggested that aberrantly expressed lncRNA PART1 is associated with the progression of various diseases, including IDD ( 36 , 17 , 18 ). Lou et al ( 38 ) revealed that lncRNA PART1 promoted the development of colorectal cancer via the miR-150-5p/leucine rich α2-glycoprotein 1 axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP2 is known to play a significant role in the process of IDD [ 41 ]. Song et al [ 34 ] found that miR-874-3p protected the intervertebral disc from degeneration by suppressing the expression of MMP2 and MMP3.…”
Section: Discussionmentioning
confidence: 99%
“…The thermocycling condition used were as follows: 95°C for 10 min followed by 40 cycles of 94°C for 15 sec, 55°C for 30 sec and 70°C for 30 sec. 20 …”
Section: Methodsmentioning
confidence: 99%